Link Budget Analysis for cmWave Communication Between LEO Satellites and Handheld User Equipment - Bhadrashetty Dinesh, Jahanvi (My University)
Abstract This master thesis report explores the viability and performance of Distributed Multiple-Input Multiple-Output (D-MIMO) systems in Low Earth Orbit (LEO) satellite constellations for a handheld user equipment (UE). A MATLAB-based link budget framework is developed to simulate the uplink and downlink scenarios between the satellites and the UE, while considering different elevation angles. Realistic assumptions from various 3rd Generation Partnership Project (3GPP) and International Telecommunications Union(ITU) standards, including those for atmospheric and rain attenuation have been used. Asymmetric power allocation procedures have been explored to optimize the reliability of the link as well as spectral efficiency. This model dynamically calculates bit error rate (BER) and signal-to-noise ratio (SNR) among others. Important parameters like Doppler shift and propagation delay are examined to assess their impact on the throughput and robustness of D-MIMO. The simulation results demonstrate that intelligent resource allocation across multiple satellites and antennas can significantly enhance the achievable data rate and reliability for next-generation satellite communication systems.
Keywords: Keywords: D-MIMO, LEO satellite communication, Link Budget Analysis, Uplink and Downlink Modelling, Signal-to-noise Ratio(SNR), Spectral Efficiency, MATLAB Simulation.